Laravel Framework-Based Parenting Application - Syahidul Haq, Mohammad; Setyowati, Nur Aini Dwi; Ashadi, Firman (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Parenting is an important and crucial thing to do because it will affect the personality, cognitive, and socio-emotional formation of children. Many studies have proven that parenting style influences the child's growth process. Therefore, the role of parents is very important at this time. The times and technological advances can be used to develop innovations that can help parents determine the right parenting style for their children. To provide a solution to this problem, the researcher conducted research and development of this Laravel Framework-Based Parenting Application, which aims to make it easy for parents to access credible information related to the world of parenting. The purpose this study is to 1.) Develop parenting applications based on Laravel Framework; (2) Calculate the feasibility of the Laravel Framework-based parenting application. This research was developed using the research and development methods by Borg and Gall, includes ten steps. Respondents in this study were determined through a random sampling technique. Testing the validity of the instrument in this study used the Pearson product moment correlation formula which was calculated using SPSS 25. The finding shows that the Laravel Framework-Based Parenting Application has been well developed and deserves to be implemented and distributed to the public. The paper also described the result of each tested categories.